2x^4+9x^3-87x^2-49x+45=0

To solve this polynomial equation, factor the left side of the equation.

(x-5)(x+1)(x+9)(2x-1)=0

Now solve for each separate term in the product.

x-5=0

x=5

x+1=0

x=-1

x+9=0

x=-9

2x-1=0

x=1/2

The solution is all values that make

(x-5)(x+1)(x+9)(2x-1) =0 true

**x=5,-1,-9,1/2**

Check by plugging the x values into the original equation one at a time.

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now